The Effect of an Autoimmune Protocol (AIP) Diet in Adults With Rheumatoid Arthritis: A Single Arm Crossover Pilot Feasibility Study - McNeill, JJ; Mearns, GJ; Grainger, R; Zinn, C (Wiley, 2026)
Background: Individuals with rheumatoid arthritis (RA) often ask whether dietary changes or food exclusions can reduce symptoms. The Autoimmune Protocol (AIP) diet, an elimination-based approach, is popular on social media, with anecdotal reports of benefit, but lacks clinical evaluation in RA. Objectives: To assess the feasibility and effectiveness of an AIP diet on patient-reported outcomes (PROs) in adults with RA. Methods: In this single-arm, open-label pilot study, nine adults with RA followed their usual diet for 4 weeks and then an 8-week AIP diet in a free-living context. Weekly PRO measures included the Routine Assessment of Patient Index Data 3 (RAPID3) and RA Impact of Disease (RAID) as primary outcomes. Secondary outcomes included 3-day weighed food records and biometric measurements (weight and waist circumference) collected at baseline and every 4 weeks. Adherence and ease of implementation were recorded weekly. Results: Nine participants (7 females, 2 males, aged 40–63 years) completed the intervention. From baseline to end week 12, mean RAPID3 scores decreased from 2.73/10 (range 0.2–5.37) to 0.99 (0–2.5). Four participants demonstrated a clinically meaningful reduction and three others reached remission from low disease activity. Mean RAID scores decreased from 3.13/10 (0.1–6.35) to 1.02 (0–2.96). Fatigue, sleep and pain improved. Mean body mass index reduced from 26.3 kg/m2 to 24.5 kg/m2. The diet was feasible with high adherence. Conclusions: An 8-week AIP diet was associated with improvements in PROs in seven of nine participants. These pilot findings support further controlled trials to confirm efficacy and explore mechanisms as a potential adjunct therapy for RA. Trial Registration: Number ACTRN12624001391561. https://www.anzctr.org.au/ACTRN12624001391561.aspx.
Keywords: AIP diet; RAID; RAPID3; autoimmune protocol diet; nutrition; patient‐reported outcomes; rheumatoid arthritis; 4205 Nursing; 42 Health Sciences; Clinical Research; Pain Research; Autoimmune Disease; Clinical Trials and Supportive Activities; Nutrition; Arthritis; Women's Health; Behavioral and Social Science; Rheumatoid Arthritis; Inflammatory and immune system; 1110 Nursing; Arthritis & Rheumatology; Humans; Arthritis, Rheumatoid; Pilot Projects; Female; Male; Middle Aged; Adult; Feasibility Studies; Cross-Over Studies; Patient Reported Outcome Measures; Humans; Arthritis, Rheumatoid; Feasibility Studies; Pilot Projects; Cross-Over Studies; Adult; Middle Aged; Female; Male; Patient Reported Outcome Measures; Humans; Arthritis, Rheumatoid; Pilot Projects; Female; Male; Middle Aged; Adult; Feasibility Studies; Cross-Over Studies; Patient Reported Outcome Measures